Neutralizing antibodies induced by homologous and heterologous boosters in CoronaVac vaccines in Chile. (April 2023) - Acevedo, Johanna; Acevedo, Mónica L.; Gaete-Argel, Aracelly; Araos, Rafael; Gonzalez, Cecilia; Espinoza, Daniela; Rivas, Solange; Pizarro, Pablo; Jarpa, Stephan; Soto-Rifo, Ricardo; Jara, Alejandro; Valiente-Echeverría, Fernando
Abstract: Objectives: To determine the impact of a booster dose on the humoral response in individuals inoculated with a complete schedule of any SARS-CoV-2 vaccine, we evaluated the neutralizing antibody (NAb) titres of homologous or heterologous booster doses over a 90-days period in CoronaVac vaccinees from 3 centres in Santiago, Chile. Methods: Individuals previously inoculated with 2 doses of CoronaVac ( N  = 523) were recruited in the context of the REFUERZO clinical trial (NCT04992182) and received either placebo ( N  = 129), or a booster dose of CoronaVac ( N  = 134), BNT162b2 ( N  = 133), or ChAdOx1 ( N  = 127). Pseudovirus neutralizing antibody titres (pVNT) were determined at baseline (day 0) as well as at days 14, 30, 60, and 90 after booster dose administration. Results: Inoculating a booster dose increases the pVNTs titres at days 14 and 30 in all groups, (13.5- and 12.0-fold increase for the CoronaVac group; 247.0- and 212.3-fold increase for the BTN162b2 group; and 89.1- and 128.1-fold increase for ChAdOx1 at each time point, respectively) with a decline observed at days 60 and 90. However, although pVNTs remained significantly higher for the BTN162b2 and ChAdOx1 groups at days 60 and 90, NAb titres reached baseline levels in the CoronaVac group at 90 days after inoculation. Discussion: A single heterologous booster (BTN162b2 or ChAdOx1) in individuals who completed the CoronaVac primary series resulted in an important increase in NAb titres remaining significantly higher at least for 90 days. These data may directly impact middle- and low-income countries currently using CoronaVac as the main vaccination strategy.